(untitled) (Fiep Bulletin - online, 2011)
The relationship between society and people with intellectual disabilities (ID) has gone through different ways throughout history. Objective: To evaluate the lifestyle and health-related physical fitness in students with learning disabilities enrolled in different grades of education. Methods: The sample comprised 79 students of both genders aged between 11 and 16 years. This is a cross-sectional study, which evaluated the lifestyle by questionnaire and physical fitness through the criteria suggested by PROESP-BR. Results: The inclusion of students had higher levels of physical fitness as well as 60% of pupils with special education not eating five servings of fruits and vegetables per day while only 29.1% of students claim the same inclusion (p.0.07) . According to the data of physical activity there is a significant difference of p <0.05 among the students. The number of individuals who exercise the inclusion is two times higher than the group of special education (80% -40%). Conclusion: Studies with larger samples should be performed, yet it may be noted that students participating in the system of inclusion are more physically fit and add less negative behavior when compared to other education systems and the sedentary lifestyle which in turn is a global trend which leads to the emergence of numerous non-communicable chronic diseases such as obesity (21), hypertension, type II diabetes among others.